2019
DOI: 10.1103/physrevlett.123.050402
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Spectrum of a Trapped Dipolar Supersolid and Its Experimental Evidence

Abstract: We study the spectrum of elementary excitations of a dipolar Bose gas in a three-dimensional anisotropic trap across the superfluid-supersolid phase transition. Theoretically, we show that, when entering the supersolid phase, two distinct excitation branches appear, respectively associated with dominantly crystal and superfluid excitations. These results confirm infinite-system predictions, showing that finite-size effects play only a small qualitative role, and connect the two branches to the simultaneous occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(176 citation statements)
references
References 60 publications
4
163
0
Order By: Relevance
“…It is possible that this energetic effect could be mitigated in systems with an overall harmonic trapping potential. We can find some evidence in this direction in recent work with a highly-magnetic atom gas in a harmonic trap (and in the absence of a lattice potential) which suggested that supersolidity was not significantly affected by finite-size effects [75]. It will be interesting for future research to address the competing effects of long-range interactions with trapping in the stability of a supersolid phase.…”
Section: Discussion and Summarymentioning
confidence: 88%
“…It is possible that this energetic effect could be mitigated in systems with an overall harmonic trapping potential. We can find some evidence in this direction in recent work with a highly-magnetic atom gas in a harmonic trap (and in the absence of a lattice potential) which suggested that supersolidity was not significantly affected by finite-size effects [75]. It will be interesting for future research to address the competing effects of long-range interactions with trapping in the stability of a supersolid phase.…”
Section: Discussion and Summarymentioning
confidence: 88%
“…Several experiments have reported the observation of the dynamical structure factor with ultracold atoms (see eg Refs. [10,[34][35][36]).…”
Section: Experimental Probe Of the Dynamical Structure Factormentioning
confidence: 99%
“…The concept of supersolidity was first introduced in the context of liquid Helium more than fifty years ago [1,2]. With ultracold atoms, supersolidity has been observed with Bose-Einstein condensates in a cavity [3][4][5][6] as well as in dipolar quantum gases [7][8][9][10]. Both experimental realizations of supersolidity are based on longrange interactions [11], a key ingredient first introduced by Gross [12].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the elementary excitations spectrum of 164 Dy and 166 Er dipolar Bose gases were analyzed in Ref. [3], by considering three-dimensional (3D) anisotropic traps across the superfluid-supersolid phase transition. The recent investigations in ultracold laboratories with two-component dipolar Bose-Einstein Condensates (BEC), on stability and miscibility properties, became quite interesting due to the number of control parameters that can be explored in new experimental setups.…”
Section: Dipolar Bose-einstein Condensate -Introductionmentioning
confidence: 99%